2023
DOI: 10.3390/ijerph20105808
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Multiple Per- and Polyfluoroalkyl Substances Exposure on Allostatic Load Using Bayesian Kernel Machine Regression

Abstract: This study aims to investigate the combined effects of per- and polyfluoroalkyl substances (PFAS) on allostatic load, an index of chronic stress that is linked to several chronic diseases, including cardiovascular disease and cancer. Using data from the National Health and Nutrition Examination Survey (NHANES) 2007–2014, this study examines the relationship between six PFAS variables (PFDE, PFNA, PFOS, PFUA, PFOA, and PFHS) and allostatic load using Bayesian Kernel Machine Regression (BKMR) analysis. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Due to the health burden caused by PFAS exposure, stress has been known to affect the body’s hormonal balance, immune function, and inflammation levels, all of which could potentially play a role in cancer development. For example, research has found a relationship between PFAS exposure and allostatic load, an index of chronic stress [ 9 , 10 , 11 ]. This indicates that the biological response to stress increases when exposed to PFAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the health burden caused by PFAS exposure, stress has been known to affect the body’s hormonal balance, immune function, and inflammation levels, all of which could potentially play a role in cancer development. For example, research has found a relationship between PFAS exposure and allostatic load, an index of chronic stress [ 9 , 10 , 11 ]. This indicates that the biological response to stress increases when exposed to PFAS.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of allostatic load, which represents the cumulative burden of chronic stress and life events, is particularly relevant here. It is hypothesized that individuals with higher allostatic load may exhibit increased sensitivity to the harmful effects of PFAS, thereby elevating their risk for endometrial cancer [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of PFAS, including PFOS and PFOA, and metals such as Pb, Cd, and Hg were investigated in this study. The study also looked at the allostatic load index using a range of clinical and bio-markers, such as albumin, creatinine clearance, BMI, triglycerides, HDL cholesterol, total cholesterol, CRP, and hemoglobin A1C [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the NHANES, a mobile exam center (MEC) gathered blood samples for laboratory processing, including evaluations for exposure to environmental agents such as PFAS and metals. Under carefully monitored circumstances, these samples were prepared, kept, and sent to laboratories around the nation [ 33 ].…”
Section: Methodsmentioning
confidence: 99%